The bank robbery analogy as a first approach for understanding basic concepts of synthesis, transport, and mechanism of action of hormones - Cardinali, Camila A.E.F.; Martins, Yandara A.; Prates, Rodrigo Pereira; de Araújo, Emmanuel Veríssimo; Viana, Felipe José Costa; de Sousa, Maria Eleticia; da Cunha Bombardi, Eduardo [UNESP]; Nunes, Maria Tereza (American Physiological Society, 2022)
Learning endocrine physiology can be challenging. Some physiological concepts are abstract, making the process of learning more difficult for students. The comprehension of basic concepts, such as chemical hormone classification, is essential to understand the differences in synthesis, secretion, transport, and mechanism of action of hormones. To assist the students on this subject, we developed an analogy between the basic concepts of hormone synthesis, transport, and mechanism of action and a bank robbery as a first approach to engage and stimulate their learning process. In the analogy, the students are asked to help identify and characterize two bank robbery crews based on a set of evidence collected by the police. The goal is to identify the general profile of lipid and water-soluble hormones synthesis, transport, and mechanism of action on target cells. When applying the activity, the students showed a great deal of interest in solving the crime and they seemed to understand the similarities between the analogy and the subject. NEW & NOTEWORTHY Two endocrine bank robbery crews are being searched by the police. As an endocrine system student, you have been summoned to help the police solve the robberies.
Keywords: Analogy; Endocrine physiology; Hormone action; Physiology education